Pemodelan Sistem Gaya Dan Traksi Roda - Bambang Sudarsono; Joni Dewanto (Institute of Research and Community Outreach, Petra Christian University, 2003)
Wheel traction is defined as vehicles' ability to push or pull the load. This magnitude depends on the power of the engine, wheel dimension, wheel load and the friction coefficient between the wheel and the road. Base on this theory, so the wheel becomes importing section in designed of vehicles' cruise ability. This report is a result of study how the wheel dimension and load was influenced on maximum traction that produce on experiments' model. The result showed that the wheel traction linearly increase since the diameter and the load of wheel increase. Abstract in Bahasa Indonesia : Traksi roda didefinisikan sebagai kemampuan suatu kendaraan untuk mendorong atau menarik beban. Besarnya tergantung dari tenaga mesin, dimensi roda, beban pada roda terhadap jalan dan koefisien gesek antara roda dengan jalan. Berdasakan teori ini maka roda menjadi bagian penting dalam merencanakan kemampuan jelajah suatu kendaraan. Laporan ini merupakan hasil studi bagaimana pengeruh dimensi dan gaya tekan roda terhadap traksi maksimum yang dihasilkan pada model uji. Hasil pengujian menunjukkan bahwa traksi roda meningkat secara linear jika diameter dan gaya tekan pada roda meningkat. Kata kunci: Roda, traksi, jelajah.